Efectos del 11/09/01 en la imaginería onírico visual y el arte - Marinovic, Mimí (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
The paper shows the results of a work about the effects of the tragic events of September 11 in the expression of oniric images across diaries of dreams and pictorial creations in a group of artists and other one of students.
Keywords: Dreams; Pictorial creation; Diary of dreams; Art therapy